Answer:
Y = 3 X + (-8)
Explanation:
The given equation is in the slope intercept form
Equation is
Y - 4 = 3 (X - 4)
In a linear function → it takes number X as a input and gives mX + b as output.
m and b are constant.
mX → it is called scaling by factor m.
+b → it is called a shift by an amount b.
Then we can say that linear function looks like this
f(X) = mX + b
Let Y = f(X)
Hence,
Y = mX + b
From the given equation
Y - 4 = 3 (X - 4)
Y - 4 = 3 X - 12
Y = 3 X + (-8) (m = 3 , b = - 8)
It is the linear form of the given equation